Glucan and resveratrol complex - possible synergistic effects on immune system - Vetvicka, Vaclav; Volny, Tomas; Saraswat-Ohri, Sujata; Vashishta, Aruna; Vancikova, Zuzana; Vetvickova, Jana (Biomedical papers, 2007)
Background: Recent data showing that glucan elicited defense responses in grapevine and induced protection via induction of resveratrol production led us to evaluate the possible synergetic effects of glucan and resveratrol complex on immune reactions.Methods: We measured phagocytosis using HEMA particles, expression of cell surface markers via fl ow cytometry, expression of cytokines using ELISA, recovery after fl uouracil-induced leucopenia and effects on gene expression via RT-PCR.Results: Our results showed that both glucan and resveratrol complex stimulated phagocytosis of blood leukocytes, caused increase in surface expression of CD+ splenocytes and showed higher restoration of spleen recovery after experimentally induced leucopenia. In all these cases, strong synergetic effects were observed. When we measured the effects of these substances on expression level of NF-κB2, Cdc42 and Bcl-2 in breast cancer cells, upregulation of Cdc42 expression was evident only using both immunomodulators in combination. Conlusions: In conclusion, our data suggest significant synergy in stimulation of immune reactions and support further studies of these natural immunomodulators.
Keywords: Glucan/Resveratrol complex/Phagocytosis/Immune reactions/Gene